To be teacher nowadays... The training teachers in a changing world - Carlinda Leite (Universidade Federal de Santa Maria, 2015)
As the title reveals, this paper points out the roles that have been assigned to teachers, acknowledging the increasing complexity of scholar education, in order to enhance the aspects to attend in teachers ́ training. The aims of this paper are, therefore, as follows: defining knowledge and abilities necessary to perform the teaching work; putting in perspective the components and procedures of teachers ́ training. Referring to these aims and basing upon the roles that have been assigned to the school and the teachers in Portugal in the last four decades,this paper builds up a reflection on the aspects to look for on teacher's training.